Long COVID: a review and proposed visualization of the complexity of long COVID - Perumal, Rubeshan; Shunmugam, Letitia; Naidoo, Kogieleum; Abdool Karim, Salim S.; Wilkins, Dave; Garzino-Demo, Alfredo; Brechot, Christian; Parthasarathy, Sairam; Vahlne, Anders; Nikolich, Janko Ž. (Frontiers in Immunology, 2023)
Post-Acute Sequelae of Severe Acute Respiratory Syndrome Coronavirus – 2 (SARS-CoV-2) infection, or Long COVID, is a prevailing second pandemic with nearly 100 million affected individuals globally and counting. We propose a framework that can be used by researchers, clinicians, and public health officials to guide the global effort toward an improved understanding of Long COVID and the eventual mechanism-based provision of care to afflicted patients. The proposed framework for Long COVID is an evidence-based, dynamic, modular, and systems-level approach to the condition. Furthermore, the framework establishes the strength of the relationships between pre-existing conditions (or risk factors), biological mechanisms, and resulting clinical phenotypes and outcomes of Long COVID. Notwithstanding the significant contribution that disparities in access to care and social determinants of health have on outcomes and disease course of long COVID, our model focuses primarily on biological mechanisms. Accordingly, the framework sets out to guide scientific, clinical, and public health efforts to better understand and abrogate the health burden imposed by long COVID.